Comparing the CO2 emissions of metered dose inhalers and dry powder inhalers: a cross-sectional environmental impact analysis of asthma and COPD therapies in South Tyrol, Italy - Giuliano Piccoliori; Jonas Mairhofer; Katia Sangermano; Günther Morandell; Adolf Engl; Christian Josef Wiedermann (BMJ Open Respiratory Research, 2025)
Introduction Inhalers for asthma and chronic obstructive pulmonary disease (COPD) are essential therapeutic interventions; however, they contribute significantly to healthcare-related CO2-equivalent (CO2eq) emissions, particularly currently used metered dose inhalers (MDIs), which use hydrofluoroalkane (HFA) propellants such as HFA-124a and HFA-227. This study quantifies the carbon footprint of inhaler utilisation in South Tyrol, Italy, and evaluates the potential CO2eq reductions achievable through the transition from MDIs to dry powder inhalers (DPIs).Methods This cross-sectional analysis used regional healthcare prescription data for inhalers dispensed in South Tyrol in 2021 and 2022, encompassing approximately 540 000 inhabitants. CO2eq emissions were calculated based on HFA content in MDIs, employing established global warming potentials, while DPI emissions were estimated from current literature values.Findings A total of 100 778 inhalers were dispensed in 2021 (45 031 MDIs, 55 747 DPIs) and 101 334 in 2022 (49 711 MDIs, 51 623 DPIs). MDIs were responsible for approximately 1000–1100 tonnes of CO2eq annually, whereas DPIs accounted for less than 55 tonnes. A transition to DPIs could potentially result in significant CO2eq reductions.Conclusions Usage of DPIs over currently used MDIs in patients who can use them could mitigate healthcare-associated global warming potential, providing a viable strategy for climate change mitigation in respiratory care. Development of low-global warming potential MDIs is a complementary strategy.